1
$\begingroup$

I have a summation of the product of two variable like this $v_{j}f_i$ where $j=1,2,\dots,d,d+1,\dots, 2d,\dots, nd$ and after each $d$ step $i$ changes from $1$ to $n$, is my notation following correct in this situation?

$$\sum_{j=1}^{nd}\sum_{i=1}^{n} v_j f^{(i)}?$$

what I mean is I want $(v_1+\dots+v_d)f^{(1)}+(v_{d+1}+\dots+v_{2d})f^{(2)}+\dots$

$\endgroup$
4
$\begingroup$

So you have $$ \begin{split} S &= (v_1+\dots+v_d)f^{(1)}+(v_{d+1}+\dots+v_{2d})f^{(2)}+\dots \\ &= f^{(1)}\sum_{k=1}^d v_k + f^{(2)}\sum_{k=d+1}^{2d} v_k + \ldots \\ &= \sum_{i=0}^n f^{(i+1)}\sum_{k=di+1}^{d(i+1)} v_k \end{split} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.